Synthesis of mesoporous RGO@(Co, Mn)3O4 nanocomposite by microwave-assisted method for supercapacitor application. (20th August 2016) - Lamiel, Charmaine; Nguyen, Van Hoa; Roh, Changhyun; Kang, ChanKyu; Shim, Jae-Jin
Graphical abstract: Highlights: Mesoporous RGO@(Co, Mn)3 O4 nanosheets were prepared by microwave-assisted method. The as-prepared electrode exhibited a high capacitance of 1004 F g −1 at 3 mV s −1 in a 6 M KOH. It exhibited an energy density of 53 Wh kg −1 at a power density of 500 W kg −1 . Abstract: Supercapacitors have attracted considerable attention because they can store more energy than conventional capacitors and can have higher power densities than batteries. In this study, microwave irradiation was used for the rapid and facile synthesis of mesoporous RGO@(Co, Mn)3 O4 oxide nanosheets as an electrode material for supercapacitor applications. The as-prepared electrode exhibited a high capacitance of 1004 F g −1 at 3 mV s −1 in a 6 M KOH electrolyte solution. Moreover, the electrode showed good specific retention and high Coulombic efficiency of 81.6% and 96.9%, respectively, after 3000 charge-discharge cycles. The electrode also exhibited a high energy density of 53 Wh kg −1 (at power density of 500 W kg −1 ) and high power density 5000 W kg −1 (at energy density of 27 Wh kg −1 ). Overall, the RGO@(Co, Mn)3 O4 electrode showed very promising results for supercapacitor applications.